PERAN PMR (PALANG MERAH REMAJA) DALAM MEMBANGUN GENERASI PANCASILA (Integralistik, 2017)
The concept of education is developed through the mechanism of the teaching-learning process called school, in which the role of the school as an intermediary link and the media of self-development, intelligence, creative imagination, and the formation of the character or character of the students. Extracurricular activities should not be positioned as a supplement, but rather a part that needs to be considered parallel to the teaching and learning activities in the classroom, because the extracurricular benefits and impact on the behavior and mindset of students, meaning that education outside the classroom has the same weight with the learning process in class. Extracurricular activities that can build the generation of Pancasila is one of them PMR. To know the activity is done through qualitative research method with technique of analysis through stages as follows: (1) Data collection; (2) data reduction; (3) Presentation of data; (4) Withdrawal of Conclusion/ Verification. The development of attitudes in accordance with the values of Pancasila is carried out through extracurricular activities of PMR covering Blood Student Donor activities (DORAS), health care in UKS, World HIV / AIDS Day, raising donations for natural disasters, Social service in the community, training with the KSR at PMI, assisting in the preparation of logistics for natural disasters at PMI. Development of attitude The planting of Pancasila principles in PMR activities is done by Moral Knowing, Moral Feeling and Moral Action. Activities carried out in extracurricular PMR provide valuable experience in real life so that it is